Relationship Between Body Composition and Nutritional Status in Brazilian Nonagenarians - Aline Oliveira Safian, Claudia; José Gonçalves Bós, Ângelo (International Journal of Nutrition, 2019)
Introduction Brazil has undergone considerable changes in age distribution, particularly in nonagenarians. Allied to this reality, there is a series of nutritional disorders in this population segment. An important factor related to quality of life and healthy aging is good nutrition throughout life. Objective To observe the possible relationship between nutritional status and body composition in nonagenarians. Methodology This is a descriptive, cross-sectional and analytical study, with participants aged 90 years or older, evaluated using the Mini Nutritional Assessment (MNA), anthropometric parameters, and Bioimpedance. Results The sample consisted of 72 nonagenarians, averaging in age 93.7 years, most female (72%), white (82%) and widowed (64%), 19.4% were in nutritional risk, based on the MNA criteria. All anthropometric parameters presented lower averages among nonagenarians in nutritional risk. Regarding the bioimpedance parameters, in general the risk-free nonagenarians presented higher averages of weight, maximum ideal weight, minimum ideal weight, BMI, lean-mass, fat-mass, percentage of fat-mass and minimum percentage of fat-mass. Conclusions Most nonagenarians were in good nutritional status. Both anthropometric and bioimpedance parameters were effective to discriminate between normal and at nutritional risk nonagenarians. We also concluded that nutritional risk assessment in nonagenarians patients requires a joint analysis of the several existing methods for the nutritional evaluation, in order to obtain global diagnosis and accurate analysis of the nutritional status of the nonagenarians.
Keywords: Anthropometry; bioimpedance; body composition; 80+ years old; public health.